2007
DOI: 10.1002/art.22877
|View full text |Cite
|
Sign up to set email alerts
|

T cells expressing allograft inflammatory factor 1 display increased chemotaxis and induce a profibrotic phenotype in normal fibroblasts in vitro

Abstract: Objective. Allograft inflammatory factor 1 (AIF-1) was first identified in rat cardiac allografts undergoing chronic rejection. The vasculopathy of chronic allograft rejection is strikingly similar to that seen in patients with systemic sclerosis (SSc). We previously demonstrated AIF-1 expression in inflammatory cells infiltrating skin and lungs from SSc patients, but its role in SSc pathogenesis is unknown. The present study was undertaken to investigate the effects of AIF-1 on T cell migration and production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 45 publications
3
33
0
Order By: Relevance
“…Expression of Aif-1 increases above basal levels in these cell types (16)(17)(18) in neuro-inflammatory disease models (19). Conceivably, increased expression of Aif-1 during EAE pathogenesis (20,21) could promote T cell, macrophage and/or microglial proinflammatory functions and overall disease activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of Aif-1 increases above basal levels in these cell types (16)(17)(18) in neuro-inflammatory disease models (19). Conceivably, increased expression of Aif-1 during EAE pathogenesis (20,21) could promote T cell, macrophage and/or microglial proinflammatory functions and overall disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Largely similar gene products arising from the same locus have been named Iba1, microglial response factor-1 (MRF1) and daintain; Iba1 in particular is a well-known histologic marker of microglia and of their activation in pathological CNS conditions. Aif-1 is differentially expressed in various mouse and human tissues (14,15) and in multiple leukocyte types including macrophages and T cells at basal levels (16)(17)(18). In inflammatory disease models, upregulated Aif-1 expression has been reported in microglia, macrophages, T cells, synoviocytes, pancreatic β-cells and adipocytes under various pathological conditions representing encephalomyelitis, uveitis, neuritis, arteriopathies, arthritis and diabetes, respectively (19).…”
Section: Loss Of Allograft Inflammatory Factor-1 Ameliorates Experimementioning
confidence: 99%
“…Daintain/AIF-1 is regarded as a novel inflammatory factor that plays important roles in allograft rejection, vasculopathy, and autoimmune diseases such as experimental autoimmune neuritis, encephalomyelitis, and uveitis models, 7,8) rheumatoid arthritis, 9) and systemic sclerosis. 10,11) Type-1 (insulin-dependent) diabetes (T1D) is characterized by a progressive autoimmune-mediated insulitis culminating in the death of pancreatic cells. The cell secretory dysfunction and apoptosis in the course of insulitis are perhaps caused by direct contact with activated macrophages and T-cells, and/or exposure to inflammatory mediators secreted by these cells, including cytokines (such as IL-1, TNF-, and IFN-) and NO.…”
mentioning
confidence: 99%
“…These factors are intricately intertwined and induce multiple clinical manifestations, but have not been elucidated in detail yet. In cells and tissues of various diseases including SSc, AIF-1 is expressed in T cells [14,15], macrophages, and endothelial cells [16,17] and may promote the expression of adhesion molecules that mediate specific homing into affected tissues [7]. Another recent study in vitro indicated that AIF-1 enhances the activation of T cells, which increase chemotaxis and induces a profibrotic phenotype [15,14], but the T cells are forcedly transfected with the vector expressing AIF-1.…”
Section: Introductionmentioning
confidence: 99%